DEGREES OF COMPARISON IN SASAK LANGUAGE AT MENO-MENE DIALECT - Rosyidi, Ahmad Zuhri; Muliadi, Mul (LPPM Institut Pendidikan Nusantara Global, 2021)
Sasak tribe is a tribe in Lombok Island that used Sasak language as their mother language. In their social life, the society of Sasak will not pass from social interaction among the people by using the language. Same as the other languages, this language has many role and grammatical which unknown yet by the other people. In this paper, the researcher will explain more about the role in Sasak language it is about degrees of comparison. In this part there are three types of degrees of comparison those are equality, comparative, and superlative. To get real grammatical in Sasak language, the researchers collected the data from the society then continued to analyze it after that the researcher got conclusions about the data. From the conclusions the researcher got the result: The first, in equality comparison, the society of Sasak use prefix ke before adjective then followed by preposition Kance. The second finding was in applying the role of comparative the adjective was added by suffix an then followed by preposition isik. And the last finding is about superlative role. In this degree the society of Sasak used word Santer or Tulen before put the adjective.